Hematoprotective effect of boron on cyclophosphamide toxicity in rats - Cengiz, Mustafa (Cellular and Molecular Biology, 2018)
The goal of this study was to determine the effects of boric acid (B) as a boron source on blood cells and indirectly on bone marrow. Intraperitoneally (i.p.) administration of 200 mg / kg of cyclophosphamide (CP) resulted in reductions in the number of erythrocyte (20%), hemoglobin (20%), leukocytes (96%), thrombocytes (41%), and hematocrit (21%). The group given CP alone was killed 3 days after the CP administrated. For the group having CP+B (200 mg/kg i.p) treatment was started 3 days earlier than the CP administration and continued to the finish of the experiment (6 days). On day 4, the animals were weighed again, relative doses of CP were expected, and CP+B was administered together. On day 7, blood samples were collected under anesthesia. The results suggest that B could reduce CP -induced toxicity on blood cells and bone marrow in rats.